Implementation of Millennial Farmer Development Policy in Bogor Regency - Casroni, Muhamad; Suryana, Asep Agus Handaka; Rusliandy, Rusliandy (Journal La Lifesci, 2024)
The development of millennial farmers has a very important role in preparing for the regeneration of farmers in the future. However, the Bogor district government has a number of weaknesses and obstacles in fostering millennial farmers. The research analyzes the implementation of millennial farmer policies in Bogor Regency from the aspects of policy context and policy content according to Grindel. The method was used with a qualitative approach, with data collection techniques using observation and interviews and data analysis using triangulation techniques. The results showed that the implementation of the millennial farmer development policy in Bogor Regency had gone well but is faced with several weaknesses and obstacles, namely socialization for agricultural extension workers is still lacking, limited budget, limited facilities and infrastructure, cross-sectoral collaboration has not been optimal and limited agricultural land ownership. The research recommendations are to increase the socialization of millennial farmer development policies, increase budgets, provide support for facilities and infrastructure, optimize cross-sector roles, and provide support and facilitation for agricultural land.